EQUITY AND THE LESSON STUDY APPROACH IN THAILAND: CURRENT AND FUTURE DIRECTIONS - Sangwanglao, Jatupol (Journal of Education and Innovation, 2024)
This paper reviews the overall development of lesson study and the possibility of implementing the concept of equity in the Thai context. Lesson study is a widely used professional development approach for Thai teachers. However, there is no clear research on the relationship between lesson study and equity in Thailand. This article provides an overview of general lesson study conceptions to help the reader understand lesson study before exploring its development in Thailand. Subsequently, the concept of equity, which is one of the themes this research highlights, is discussed. The theoretical and practical relationships between lesson study and equity are then further examined before analyzing the research trends on this topic. The investigation shows that implementing equity issues through the lesson study approach is possible in the Thai context. Future research should further develop the notion of equity as part of an action plan to improve the lesson study approach and make it more sustainable.